Interfacial 2-hydrozybenzophenone passivation for highly efficient and stable perovskite solar cells - Foo, Shini (2022)
Defects found on the surfaces of organic-inorganic perovskite films are detrimental to the device efficiency, reproducibility and stability. Herein, 2-hydrozybenzophenone (HBP) is introduced to the perovskite/spiro-OMeTAD interface in which the optimized device shows superior power conversion efficiency of 19.28% and long-term stability in which 93% of initial efficiency is retained, despite having been stored for 120 days. Improvements are attributed to the reduction in surface defects and strengthened charge transport properties, which are supported by the enhanced open-circuit voltage and fill factor, respectively. Acting as a Lewis base molecule, effective interactions between HBP and under-coordinated lead ions passivate the surface defects found on the perovskite film, allowing increase in both device efficiency and durability. The increased hydrophobicity further improves the stability of the device. Hence, this work provides a facile yet highly effective approach for achieving high efficiency, reproducibility and stability in planar perovskite solar devices.